Zika Virus: the Latest Newcomer - Saiz, Juan-Carlos; Vázquez-Calvo, Ángela; Blázquez, Ana B.; Merino-Ramos, Teresa; Escribano-Romero, Estela; Martín-Acebes, Miguel A. (Frontiers in Microbiology, 2016)
Since the beginning of this century, humanity has been facing a new emerging, or re-emerging, virus threat almost every year: West Nile, Influenza A, avian flu, dengue, Chikungunya, SARS, MERS, Ebola, and now Zika, the latest newcomer. Zika virus (ZIKV), a flavivirus transmitted by Aedes mosquitoes, was identified in 1947 in a sentinel monkey in Uganda, and later on in humans in Nigeria. The virus was mainly confined to the African continent until it was detected in south-east Asia the 1980´s, then in the Micronesia in 2007 and, more recently in the Americas in 2014, where it has displayed an explosive spread, as advised by the World Health Organization (WHO), which resulted in the infection of hundreds of thousands of people. ZIKV infection was characterized by causing a mild disease presented with fever, headache, rash, arthralgia, and conjunctivitis, with exceptional reports of an association with Guillain-Barre syndrome (GBS) and microcephaly. However, since the end of 2015, an increase in the number of GBS associated cases and an astonishing number of microcephaly in foetus and new-borns in Brazil have been related to ZIKV infection, raising serious worldwide public health concerns. Clarifying such worrisome relationships is, thus, a current unavoidable goal. Here, we extensively review what is currently known about ZIKV, from molecular biology, transmission routes, ecology and epidemiology, to clinical manifestations, pathogenesis, diagnosis, prophylaxis and public health.